Most relevant clinical supervision strategies in nursing practice - Pires, Regina (2016)
Clinical supervision (CS) is a facilitator of professional development and quality of practice, promoting safety and protection of clients, through the adoption of targeted strategies. Portugal has been developing research aiming to design policies that support the implementation of CS based on partnerships between academic and practice nurses. This strategy empowers professionals with skills essential for professional development. The study aims to identify the most relevant CS strategies according to nurses’ perspective. A quantitative and exploratory study was developed. Data were collected from questionnaires between May and October 2012. The convenience sample included 273 nurses working in hospitals (64.3%) and health care centers (35.7%) in Portugal, 83.2% were females, aged between 24-58 years. Nursing professional experience ranged between 1-36 years. The majority of the participants (87.5%) considered CS important to professional development. CS strategies relevance: reflective practice (45.8%); feedback (45.8%); observation (45.1%); continuing education (44,3%); support (41.8%); demonstration (40.7%); individual sessions (37.4%); self-supervision (37.0%); cases analysis with supervision (31.9%); analysis of nursing documentation (30.8%); group cases analysis (22.7%); group sessions (21.6%), reflexive report (16.5%); distance supervision: e-mail (7.7%), phone (7.7%) and skype® (4.0%). The participation of nurses in the design of CS policies is considered meaningful and highly relevant to nursing practice, empowering nurses with qualified skills and contributing to improve the quality of interventions. This research is a valuable input to the development and innovation in nursing, contributing to the design of CS policies based on strategies that nurses consider more appropriate and relevant to practice and professional development.